Gut Metabolite TMAO Induces Synaptic Plasticity Deficits by Promoting Endoplasmic Reticulum Stress - Govindarajulu, Manoj; Pinky, Priyanka D.; Steinke, Ian; Bloemer, Jenna; Ramesh, Sindhu; Kariharan, Thiruchelvan; Rella, Robert T.; Bhattacharya, Subhrajit; Dhanasekaran, Muralikrishnan; Suppiramaniam, Vishnu; Amin, Rajesh H. (Frontiers in Molecular Neuroscience, 2020)
Dysbiosis of gut microbiota is strongly associated with metabolic diseases including diabetes mellitus, obesity, and cardiovascular disease. Recent studies indicate that Trimethylamine N-oxide (TMAO), a gut microbe-dependent metabolite is implicated in the development of age-related cognitive decline. However, the mechanisms of the impact of TMAO on neuronal function has not been elucidated. In the current study we investigated the relationship between TMAO and deficits in synaptic plasticity in an Alzheimer’s model (3xTg-AD) and an insulin resistance (Leptin deficient dbdb) mouse by measuring plasma and brain levels of TMAO. We observed increased TMAO levels in the plasma and brain of both dbdb and 3xTg-AD mice in comparison to wild-type mice. In addition, TMAO levels further increased as mice progressed in age. Deficits in synaptic plasticity, in the form of reduced long-term potentiation were noted in both groups of mice in comparison to wild-type mice. To further explore the impact of TMAO on neuronal function, we utilized an ex-vivo model by incubating wild-type hippocampal brain slices with TMAO and found impaired synaptic transmission. We observed that TMAO induced the PERK-EIF2α - ER stress signaling axis in TMAO treated ex-vivo slices as well as in both dbdb and 3xTg-AD mice. Lastly, we also observed altered presynaptic and reduced post synaptic receptor expression. Our findings suggest that TMAO may induce deficits in synaptic plasticity through ER stress mediated PERK signaling pathway. Our results offer novel insight into the mechanism by which TMAO may induce cognitive deficits by promoting ER stress and identifies potential targets for therapeutic intervention.